2016
DOI: 10.1002/2015ja022303
|View full text |Cite
|
Sign up to set email alerts
|

Polytropic index of magnetosheath ions based on homogeneous MHD Bernoulli Integral

Abstract: This paper uses Cluster data during the period from 2001 to 2010 to study the polytropic processes of magnetosheath ions. Utilizing the method of homogeneous magnetohydrodynamic (MHD) Bernoulli integral (MBI), we first identify streamflow tubes, then use the constant of polytropic relation to guarantee that the streamflow tube experiences an unchanged polytropic process, and finally determine the polytropic index of ions in these streamflow tubes. The statistical results show that the magnetosheath is a compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…Zhu (1990) statistically analyzed the data of plasma number density and pressure measured by ISEE satellite from and found that the polytropic index in the CPS is 1.08 for AE < 100 nT and 1.31 for AE > 100 nT, respectively. The approach of MHD Bernoulli Integral is considered to be one of the best methods to calculate polytropic index since it can guarantee that the used data come approximately from the same unit (Kartalev et al, 2006;Nicolaou et al, 2014;Pang et al, 2016). The approach of MHD Bernoulli Integral is considered to be one of the best methods to calculate polytropic index since it can guarantee that the used data come approximately from the same unit (Kartalev et al, 2006;Nicolaou et al, 2014;Pang et al, 2016).…”
Section: 1029/2019ja026681mentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu (1990) statistically analyzed the data of plasma number density and pressure measured by ISEE satellite from and found that the polytropic index in the CPS is 1.08 for AE < 100 nT and 1.31 for AE > 100 nT, respectively. The approach of MHD Bernoulli Integral is considered to be one of the best methods to calculate polytropic index since it can guarantee that the used data come approximately from the same unit (Kartalev et al, 2006;Nicolaou et al, 2014;Pang et al, 2016). The approach of MHD Bernoulli Integral is considered to be one of the best methods to calculate polytropic index since it can guarantee that the used data come approximately from the same unit (Kartalev et al, 2006;Nicolaou et al, 2014;Pang et al, 2016).…”
Section: 1029/2019ja026681mentioning
confidence: 99%
“…Pang et al (2015aPang et al ( , 2015b adopted the approach of MHD Bernoulli integral and found that the polytropic index of background plasma sheet ions have a wide distribution around γ~1.0. The approach of MHD Bernoulli Integral is considered to be one of the best methods to calculate polytropic index since it can guarantee that the used data come approximately from the same unit (Kartalev et al, 2006;Nicolaou et al, 2014;Pang et al, 2016). Baumjohann and Paschmann (1989) also show that the polytropic index is 1.39 in the quiet (AE < 100 nT) plasma sheet and 1.64 in the active (AE > 100 nT) plasma sheet, respectively.…”
Section: 1029/2019ja026681mentioning
confidence: 99%
“…Therefore, the polytropic index can be estimated from either the number density‐thermal pressure ( n ‐ p ) relation or the number density‐temperature ( n ‐ T ) relation. Using the linear fit between the logarithms of number density and those of thermal pressure (or temperature), previous studies examined thermodynamic conditions for plasmas in the various regions near the terrestrial magnetosphere, such as the interplanetary space (Kartalev et al, ; Newbury et al, ; Nicolaou et al, ), the magnetosheath (Pang et al, ; Song et al, ), and the plasma sheet (Baumjohann & Paschmann, ; Frühauff et al, ; Huang et al, ; Pang et al, ; Zhu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Pudovkin et al () and Meister et al () examined the thermodynamic properties for magnetized anisotropic plasma using the anisotropic magnetohydrodynamics (MHD) with the double‐adiabatic law and suggested that the effective polytropic index, which is characterized by the relationship between the total thermal energy and the number density of the plasma in their studies, depends both on the characteristics of the plasma flow and on the temperature anisotropy. Using the polytropic relation and Bernoulli's theorem, Pang et al () examined the polytropic indices for magnetosheath ions estimated along the same streamline and found that their probability distribution has a major peak near 1 (that is, quasi‐isothermal process) with a minor peak near 0 (that is, quasi‐isobaric process). Moreover, they suggested that the isobaric process for magnetosheath ions is attributed to the electromagnetic energy, which exchanges across the streamlines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation